DIGITAL TRANSFORMATION THROUGH SOCIAL MEDIA – A STUDY - Amruthamma R; Bharathi K V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose: social media through digitalization is acquiring vital significance in the competitive business scenario. Internet provides a simple & standardized method for companies to advertise their goods & services to consumers. To what extent do socioeconomic features affect research into digitalization & social media is primary goal of this work and further to probe the uses of both social media and digitalization, and factors driving companies to use social media and digitalization. The study also conducted to know the impact of social media & digitalization upon respondents for buying fashion apparels. Methodology / Design: Necessity to prevent late response, non-response, & incompleteness lead to administration of well crafted questionnaire on time. A total of 108 questionnaires had been approached & out of 108 questionnaires just 100 were found to be useful forming a success rate of 92.59% x2, contingency co-efficient, weighted arithmetic mean, & Garrett Ranking technique have been utilized to process the collateral data. Findings: The research found that there is a strong correlation between demographic and socioeconomic factors and the degree to which they have digitized their economies. Building brand reputation, taking the people opinion about the product and youngster rely on mobile gadgets through social media are the preferred uses of social media and digitalization. Factors like message spread, reduction in the use of cashless transactions and faster communication preference are some of the drivers of companies forcing to use social media and digitalization is tend through the preferred drivers like social media drives impulse buying, inspiration source and parental influence to lead more digital life.